2020
DOI: 10.1002/essoar.10503971.1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

NOx emissions reduction and rebound in China due to the COVID-19 crisis

Abstract: During the COVID-19 lockdown (24 January-20 March) in China low air pollution levels were reported in the media as a consequence of reduced economic and social activities. Quantification of the pollution reduction is not straightforward due to effects of transport, meteorology, and chemistry. We have analyzed the NO x emission reductions calculated with an inverse algorithm applied to daily NO 2 observations from TROPOMI onboard the Copernicus Sentinel-5P satellite. This method allows the quantification of emi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
36
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 25 publications
(36 reference statements)
5
36
0
Order By: Relevance
“…Guevara et al (2020), or Barré et al (2020) report European emissions reductions up to 60% for NOx, and up to 15% for Non-Methane Volatile Organic Compounds (NMVOC) in March/April 2020. Based on satellite observations of NO2 columns (Bouwens et al, 2020), comparable NOx emissions reductions are reported for Chinese cities in February 2020 (Ding et al, 2020;. Globally averaged CO2 emissions decreased by 8.8% during the first half of 2020 (Liu et al, 2020), consistent in timing and magnitude with the aforementioned NO2 emission reductions.…”
Section: Introductionsupporting
confidence: 63%
“…Guevara et al (2020), or Barré et al (2020) report European emissions reductions up to 60% for NOx, and up to 15% for Non-Methane Volatile Organic Compounds (NMVOC) in March/April 2020. Based on satellite observations of NO2 columns (Bouwens et al, 2020), comparable NOx emissions reductions are reported for Chinese cities in February 2020 (Ding et al, 2020;. Globally averaged CO2 emissions decreased by 8.8% during the first half of 2020 (Liu et al, 2020), consistent in timing and magnitude with the aforementioned NO2 emission reductions.…”
Section: Introductionsupporting
confidence: 63%
“…While emissions can be estimated from satellite observations using data-driven methods (Beirle et al, 2019, Beirle et al, 2021Fioletov et al, 2016;Goldberg et al, 2019) or using complex inverse modelling techniques (e.g. Millet et al, 2008;Stavrakou et al, 2009;Bauwens et al, 2016;Ding et al, 2020;Miyazaki et al, 2020;Borsdorff et al, 2019;Borsdorff et al, 2020), here we use a more qualitative approach to probe emission changes. First we compare the concentrations in 2020 with those from the same period from earlier years and then carry out additional analysis to separate the lockdown-driven variability from seasonal and meteorological variability taking in account emission changes driven by mechanisms.…”
Section: Understanding and Interpreting Tropomi Trace Gas Retrievalsmentioning
confidence: 99%
“…Undoubtedly, nearly globally implemented social distancing and isolation measures have resulted in a significant reduction of air pollution (Bauwens et al., 2020; Ding et al., 2020; European Space Agency, 2020; NASA, 2020; Navinya et al., 2020; Nikkei Asian Review, 2020; Querol et al., 2007; Shi & Brasseur, 2020; P. Wang et al., 2020). These statistics of air quality improvements are commonly reported by comparing the restricted human activity periods with the “normal conditions,” months or years before the sanitary emergency with no way to estimate the reliability of these results.…”
Section: Introductionmentioning
confidence: 99%